2016
DOI: 10.1182/blood.v128.22.283.283
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between CEBPA bZIP and TAD Mutations and Their Effect on Outcome-an Analysis in 4578 Patients with Acute Myeloid Leukemia

Abstract: Mutations of the key myeloid transcription factor CCAAT/enhancer binding protein alpha (C/EBPa) are found in 5-10% of patients with acute myeloid leukemia (AML). Two mutational clusters exist, in the aminoterminal transcription activation domains (TAD1 or 2) and in the basic leucine zipper domain (bZIP) located at the carboxyterminal-part of the protein. Biallelic mutations (biCEBPA) have been found to be associated with improved outcome and are now included as an independent entity in the WHO-classification. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
3
7
0
Order By: Relevance
“…In this large cohort of 2948 children and young adults with newly diagnosed AML, we demonstrated that patients with CEBPA mutations that had single bZip domain mutations experienced outcomes nearly identical to those of patients with biallelic CEBPA mutations. Our findings align with those of Georgi et al 24 who reported on a cohort of 4578 adult patients with AML and showed analogous outcomes for patients with CEBPA-dm and CEBPA-bZip. Our study provides more definitive support that the presence of a CEBPA-bZip mutation is associated with favorable outcome, regardless of monoallelic or biallelic status.…”
Section: Discussionsupporting
confidence: 92%
“…In this large cohort of 2948 children and young adults with newly diagnosed AML, we demonstrated that patients with CEBPA mutations that had single bZip domain mutations experienced outcomes nearly identical to those of patients with biallelic CEBPA mutations. Our findings align with those of Georgi et al 24 who reported on a cohort of 4578 adult patients with AML and showed analogous outcomes for patients with CEBPA-dm and CEBPA-bZip. Our study provides more definitive support that the presence of a CEBPA-bZip mutation is associated with favorable outcome, regardless of monoallelic or biallelic status.…”
Section: Discussionsupporting
confidence: 92%
“…Acute myeloid leukaemia has a 5-year survival rate of 25% (Georgi et al, 2016). Clinical evidence continues to support the need to identify novel targets and therapeutics for the treatment of this deadly disease.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of CEBPA mainly located on the TAD domain of C‐terminal or b‐ZIP domain of N‐terminal of alleles. It was reported recently that the patients with CEBPA b‐ZIP monoallelic mutations had superior survival and the ones with CEBPA TAD monoallelic mutations had poor outcome . In our 13 cases with CEBPAmo mutations, six were mutated in b‐ZIP domain and three in TAD domain, all of them presented poor survival.…”
Section: Discussionmentioning
confidence: 61%